Characterization of Black Bengal goat - Paul, S; Khandoker, MAMY; Moinuddin, MA; Paul, RC (Journal of the Bangladesh Agricultural University, 2011)
Characterization of Black Bengal bucks and does was performed in this study. A total of 50 goats of different aged were studied. The experiment was performed in Black Bengal bucks and does at 1st day and at 3, 6, 9 and 12 months of age for measuring different parameters such as body length, heart girth, wither height, hip height, fore and hind leg length, head length and width, head length and width, ear length and ear breath, scrotal length and scrotal circumference. In a single parameter as body weight of Black Bengal bucks and does at 1st day and at 3, 6, 9 and 12 months of age were found to be 1.08±0.06, 5.22±0.33, 8.95±0.34, 12.05±0.47 and 14.20±0.20; and 1.01±0.23, 3.93±0.19, 7.41±0.27, 9.53±0.38 and 12.40±0.41 kg respectively. Whereas all the finding where gradually increased for all parameters according to their specific age periods. Body weight has a strong positive relationship with heart girth, body length, height at wither, scrotal length and scrotal circumference in Black Bengal goat. All the parameters studied found comparatively higher in bucks than does. Keywords: Black Bengal goat; Characterization; Body parts; Analysis DOI: http://dx.doi.org/10.3329/jbau.v9i1.8745 JBAU 2011; 9(1): 61-66